External and internal training load comparison between sided-game drills in professional soccer - Beato, Marco; de Keijzer, Kevin L; Costin, Andrew J (Frontiers in Sports and Active Living, 2023)
This study aims to quantify and compare the external and internal training load demands of sided-game drills in professional team players during the competitive season. Twenty-four male professional soccer players of the same club were enrolled in this study. Drills were categorized as large-sided games (LSG): 10vs10 (84 × 60 m or 72 × 60 m), Hexagon possession 9vs9 + 3 (36 × 48 m), Possession gate 8vs8 + 2 (36 × 44 m), Possession 7vs7 + 3 (30 × 32 m) or as Small-sided games (SSG): 6vs6 (48 × 42 m), and Possession 6vs4 (30 × 60 m). A total of 7 drills and 279 individual data points were included in this analysis. Distance covered, high-speed running (HSR), and sprinting distance were all calculated in meters per minute (m.min−1) while total accelerations (>3 m.s−2) and total decelerations (− < 3 m.s−2) were calculated in number of actions per minute (n.min−1). All external load was measured with global navigation satellite systems (GNSS) STATSports Apex units. Players’ internal load was quantified using their rating of perceived exertion (RPE). We found that distance covered (p < 0.01, large), HSR (p < 0.01, large), and sprinting distance (p < 0.01, large) changed between drills (e.g., greater in LSG formats), acceleration (p < 0.01, large) and deceleration (p < 0.01, large) demands were greater in smaller formats (e.g., SSG 6vs6, and Possession 6vs4), while RPE was lower in the Possession gate 8vs8 + 2 format (p < 0.01, large). This study found that sided-games can replicate and sometimes exceed some match-specific intensity parameters, however, HSR and sprinting were consistently lower compared to official matches.